PARTICIPATION OF THE YOUNG GENERATION AS MEMBERS OF THE 2024 ELECTION KPPS: CASE STUDY IN KALIREJO VILLAGE, SALAMAN DISTRICT, MAGELANG REGENCY - Pelawi, Etatania Br; Sinuraya, Suci Iriani; Winanta, Rizza Arge; Wismaningtyas, Tri Asih (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
This research is motivated by the phenomenon of high participation of the younger generation as members of the KPPS in the 2024 Election in Kalirejo Village, Salaman District, Magelang Regency. This research uses a qualitative method. The results of the study show that the majority of the young generations participation as members of KPPS in Kalirejo Village is included in the type of participation compelled by socio-economic reasons. Then followed by spontaneous participation and induced participation. Other types of participation, such as participation compelled by custom/tradition only appear in a small percentage of the younger generation and are situational. Meanwhile, participation compelled by law can be said not to be found in the participation of the younger generation as members of KPPS in Kalirejo Village. The supporting factors for this participation are personal awareness or intrinsic motivation, support from other parties (extrinsic motivation), as well as the existence of financial incentives (honorarium) and the need for productive activities. Then, the inhibiting factors are lack of interest or political awareness, work constraints, obstacles to family licensing and having family members who cannot be abandoned, as well as incompatibility of educational qualifications.